An investigational back surface cooling approach with different designs of heat‐absorbing pipe for PV/T system. (2nd February 2018) - Bhattacharjee, Subhadeep; Acharya, Shantanu; Potar, Anil; Meena, Anurag; Bairwa, Dhara Singh; Meena, Dinesh; Bhagora, Manish; Meena, Pukhraj; Gautam, Prashant Kumar
Summary: A solar photovoltaic panel accumulates substantial amount of heat, which deteriorates its performance. Thus, to minimize the panel temperature, 3 new designs (semioval serpentine, circular spiral, and circular spiral semiflattened) of absorbers for back surface cooling are introduced in this paper. Experimental investigations on the panel performances with and without the designed cooling systems are performed. A similar experiment with an existing serpentine design of absorbers is also conducted, and the results of all the experiments are compared. The circular spiral semiflattened design absorber has shown preeminent performance among all the absorbers in terms of the highest improvement in efficiency (4.32%), fill factor (19.80%), etc. Abstract : This paper presents an experimental study on 3 new simple designs of absorbers along with an existent one, for back surface cooling of photovoltaic panels. Investigations on the panel performances with and without cooling systems are made, and the results of all the experiments are compared. Best cooling is achieved from the circular spiral‐shaped semiflattened copper pipe design, introduced in the study. Consequently, the best improvement in performance of the photovoltaic panel is observed during the experiment with this design.